(1)2(4x-0.5)
(2)3x-x-5x
(3)-x+(2x-2)-(3x+5)
(4)3a的2次方+a的2次方-(2a的2次方-2a)+(3a-a的2次方)
(5)x-(3x-2)+(2x-3)
(6)(3a的2次方+a-5)-(4-a+7a的2次方)
(7)(2m-3)+m-(3m-2)
(8)3(4x-2y)-3(-y+8x)
8道都要有过程,我坚决不选只有答案的,我要他的过程
(1)2(4x-0.5)
(2)3x-x-5x
(3)-x+(2x-2)-(3x+5)
(4)3a的2次方+a的2次方-(2a的2次方-2a)+(3a-a的2次方)
(5)x-(3x-2)+(2x-3)
(6)(3a的2次方+a-5)-(4-a+7a的2次方)
(7)(2m-3)+m-(3m-2)
(8)3(4x-2y)-3(-y+8x)
8道都要有过程,我坚决不选只有答案的,我要他的过程
解:
(1)原式=2×4x-2x0,5
=8x-1
(2)原式=(3-1-5)x
=-3x
(3)原式=-x+2x-2-3x-5
=(-1+2-3)x-7
=-2x-7
(4)原式=(3+1-2-1)a^2+(2+3)a
=a^2+5a
(5)原式=(1-3+2)x+2-3
=-1
(6)原式=(3-7)a^2+(1+1)a-5-4
=-4a^2+2a-9
(7)原式=(2+1-3)m-3+2
=-1
(8)原式=12x-6y+3y-24x
=(12-24)x+(-6+3)y
=-12x-3y
2(4x-0.5)
解:原式=2×4x-2×0.5
=8x-1
3x-x-5x
解:原式= -3x
-x+(2x-2)-(3x+5)
解:原式= -x+2x-2-3x-5
= -x+2x-3x-2-5
= -2x-7
3a²+a²-(2a²-2a)+(3a-a²)
解:原式= 3a²+a²-2a²+2a+3a-a²
=a²+5a
x-(3x-2)+(2x-3)
解:原式=x-3x+2+2x-3
=4x-1
(3a²+a-5)-(4-a+7a²)
解:原式=3a²+a-5-4+a-7a²
=-4a²+2a-9
(2m-3)+m-(3m-2)
解:原式=2m-3+m-3m+2
=2m+m-3m-3+2
= -1
3(4x-2y)-3(-y+8x)
解:原式=12x-6y-(-3y+24x)
=12x-6y+3y-24x
=12x-24x-6y+3y
= -12x-3y
请采纳.谢谢!
(1) 2(4x-0.5) (2) 3x-x-5x =2×4x-2×0.5 =-3x =8x-1
(3) -x+(2x-2)-(3x+5) (4) 3a^2+a^2-(2a^2-2a)+(3a-a^2) =-x+2x-2-3x-5 =4a^2-2a^2+2a+9a^2-a^2 =-2x-7 =10a^2+2a
(5) x-(3x-2)+(2x-3) (6) (3a^2+a-5)-(4-a+7a^2)
=x-3x+2+2x-3 =3a^2+a-5-4+a-7a^2
=-2x-1 =2a^2+2a-9
(7)(2m-3)+m-(3m-2) (8) 3(4x-2y)-3(-y+8x)
=2m-2+m-3m+2 =12x-6y+3y-24x
=-1 =-12x-3y